2020
DOI: 10.1186/s12964-019-0503-7
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3 like 1 suppresses the stability and activity of p53 to promote lung tumorigenesis

Abstract: Background: Chitinase 3 like 1 protein (Chi3L1) is expressed in several cancers, and a few evidences suggest that the secreted Chi3L1 contributes to tumor development. However, the molecular mechanisms of intracellular Chi3L1 are unknown in the lung tumor development. Methods: In the present study, we generated Chi3L1 knockout mice (Chi3L1 KO(−/−) ) using CRISPR/Cas9 system to investigate the role of Chi3L1 on lung tumorigenesis. Results:We established lung metastasis induced by i.v. injections of B16F10 in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…The NGS results showed downregulation of JAK/STAT and PI3K/AKT/mTOR genes in TQ-treated cells. The results also revealed significant downregulation in genes that induced the activation of JAK/STAT and PI3K/AKT/mTOR pathways ( Figure 11 ) such as chemokine (C–C motif) ligand 2 ( CCL2 ) [ 36 ], colony-stimulating factor 1 receptor ( CSF1R ) [ 37 ], CXC chemokine receptor 2 ( CXCR2 ) [ 38 ], interleukin 6 receptor (IL6R) [ 39 ], G protein-coupled receptors (GPCRs) [ 40 ], and chitinase 3 like 1 protein (Chi3L1) [ 41 ]. These findings suggest that TQ induces apoptosis and inhibits cancer cell proliferation by inhibiting the JAK/STAT and PI3K/AKT/mTOR signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The NGS results showed downregulation of JAK/STAT and PI3K/AKT/mTOR genes in TQ-treated cells. The results also revealed significant downregulation in genes that induced the activation of JAK/STAT and PI3K/AKT/mTOR pathways ( Figure 11 ) such as chemokine (C–C motif) ligand 2 ( CCL2 ) [ 36 ], colony-stimulating factor 1 receptor ( CSF1R ) [ 37 ], CXC chemokine receptor 2 ( CXCR2 ) [ 38 ], interleukin 6 receptor (IL6R) [ 39 ], G protein-coupled receptors (GPCRs) [ 40 ], and chitinase 3 like 1 protein (Chi3L1) [ 41 ]. These findings suggest that TQ induces apoptosis and inhibits cancer cell proliferation by inhibiting the JAK/STAT and PI3K/AKT/mTOR signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…18 19 It is also unclear whether high levels of CHI3L1 can inhibit NK cells, hindering their role as sentinels and enabling the development of CHI3L1-mediated metastatic disease. [20][21][22][23][24][25] As opposed to their prime role in controlling metastasis formation, NK cells have been generally considered as minor players in the control of solid tumors. 26 However, this concept has been challenged by the use of ADCC-inducing monoclonal antibodies (eg, Trastuzumab, Cetuximab), immune-checkpoint blockers, NK cell engagers, and chimeric receptors that enhance NK cell cytotoxicity and redirect them to treat solid malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…and can be used as an inflammatory biomarker [21,22] . YKL40 has also been found to be associated with a high risk of cancer progression and future cancer development [9,10,23] KRT5 is widely expressed in cancer tissues and can promote cancer cell growth, migration [11,24] and increase mortality in cancer patients. Xiao et al [25] found KRT5 to be valuable in the diagnostic differential of lung adenocarcinoma and lung squamous cell carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the detection of biomarkers in alveolar lavage fluid or serum is a new method for the early diagnosis of lung cancer, which is promising due to its simplicity, reproducibility and low invasiveness [8] . Recent studies have shown that Chitinase-3-like protein 1 (YKL-40) and Keratin 5 (KRT5) play an important role in the staging, differential diagnosis and prognosis of lung cancer [9][10][11] , but most of the studies have been conducted on a single tumor marker and there are few reports on the simultaneous detection of the expression levels of both in alveolar lavage fluid. The aim of this study was to explore the value of YKL40 and KRT5 in Bronchoalveolar Lavage Fluid (BALF) for the early diagnosis of lung cancer.…”
mentioning
confidence: 99%